Stochastic Model of Acidification, Activation of Hemagglutinin and Escape of Influenza Viruses from an Endosome - Lagache, Thibault; Sieben, Christian; Meyer, Tim; Herrmann, Andreas; Holcman, David (Frontiers in Physics, 2017)
Influenza viruses enter the cell inside an endosome. During the endosomal journey, acidification triggers a conformational change of the virus spike protein hemagglutinin (HA) that results in escape of the viral genome from the endosome into the cytoplasm. It is still unclear how the interplay between acidification and HA conformation changes affects the kinetics of the viral endosomal escape. We develop here a stochastic model to estimate the change of conformation of HAs inside the endosome nanodomain. Using a Markov process, we model the arrival of protons to HA binding sites and compute the kinetics of their accumulation. We compute the Mean First Passage Time (MFPT) of the number of HA bound sites to a threshold, which is used to estimate the HA activation rate for a given pH concentration. The present analysis reveals that HA proton binding sites possess a high chemical barrier, ensuring a stability of the spike protein at sub-acidic pH. We predict that activating more than 3 adjacent HAs is necessary to trigger endosomal fusion and this configuration prevents premature release of viruses from early endosomes